A Pilot Clinical Study on the Accuracy and Safety of Ultrasound-guided Gyeontonghyeol (BP-LE6) Acupuncture: A Prospective Randomized, Single Blinded Crossover Study - Jong Uk Kim; Bo Hyun Kim; Seok Hee Kim; Jin Hyeon Shin; Yoo Min Choi; Beom Yong Song; Tae Han Yook; Young Ju Jeon; Sanghun Lee (MEDrang Inc., 2019)
Background The purpose of this study was to assess the accuracy and safety of procedures using ultrasound equipment for acupuncture treatment. Methods A pilot, prospective randomized, single blinded, crossover clinical study on the accuracy and safety of ultrasound-guided Gyeontonghyeol; (BP-LE6) acupuncture treatment was conducted. Patients (n; = 13) with shoulder pain were randomly divided into 2 groups. During Visit 1, ultrasound-guided BP-LE6 acupuncture was administered to the experimental group. In the control group, patients received BP-LE6 acupuncture (without checking ultrasound images) by manipulating the ultrasound probe as if administering ultrasound-guided acupuncture. Visit 2 was arranged within 7-14 days and the remaining procedures, other than those administered in Visit 1, were performed. In both the experimental group and control group, the number of needle insertions, and time required for the treatment to result in the patients feeling de-qi; was recorded. The numeric rating scale (NRS) score for shoulder pain was recorded before and after the acupuncture treatment. Results The number of needle insertions was 5.31 ± 3.50 times in the experimental group, and 6.62 ± 3.38 times in the control group, however, there was no statistically significant difference between the groups (p; > 0.05). The mean time required to perform the procedure was 151.54 ± 48.59 seconds in the experimental group and 86.69 ± 37.17 seconds in the control group, which was statistically significantly different (p; < 0.05). The changes observed in numerical rating scale scores between groups were not statistically significantly different. Conclusions Although there was no statistically significant difference, administering acupuncture using ultrasound guidance may lead to accurate needling with a reduced number of needle insertion attempts. A large-scale clinical study of better design should be conducted in the future.